Pengaruh Komunikasi Organisasi, Modal Psikologi, Keterlibatan Kerja, Kepuasan Kerja dan Budaya Organisasi terhadap Komitmen Organisasi Pada Karyawan Puskesmas - Haryanto, Jepri; Rianto, Sugeng (STIE Bangkinang Publishing, 2025)
This study aims to determine and analyze the influence of organizational communication, psychological capital, work involvement, job satisfaction, and organizational culture on organizational commitment at the Bumiayu District Health Center. This study was conducted on all employees of the Bumiayu Health Center excluding doctors. The method used in this study is a quantitative approach. The data used in this study are primary data with data collection techniques by distributing questionnaires to respondents. The sample in this study amounted to 97 respondents. The sampling technique used probability sampling with a random sampling method. The data analysis technique in this study used instrument testing (validity testing, reliability testing, descriptive analysis (scoring techniques with a Likert scale of 1-5), classical assumption testing (normality testing, heteroscedasticity testing, multicollinearity testing) and multiple linear regression analysis (t-test, f-test, coefficient of determination) using SPSS V.25. Based on the results of this study, it shows that psychological capital, work involvement, job satisfaction, and organizational culture have a positive effect on organizational commitment, while organizational communication does not affect organizational commitment